Development of Hybrid Learning Management System to Improve the Quality of Lectures at Sayyid Ali Rahmatullah State Islamic University Tulungagung - Anam, Khoirul; Asyhar, Beni (Didaktika Religia, 2023)
This article aims to develop a learning management system product as an effort to improve the quality of hybrid lectures at UIN SATU Tulungagung. The development of information and communication technology in the 21st century encourages the emergence of various learning innovations. This is an alternative in overcoming various conventional learning problems. One of the learning innovation products that adapt the utilization of information and communication technology is e-learning. E-learning is a learning model that utilizes internet technology in a very wide range. These innovations aim to improve the quality of learning. Therefore, the development and utilization of e-learning is important. This article is written based on research and product development with ADDIE model. This article produces an e-learning application in the form of a Learning Management System that can accommodate user needs and can be adjusted to the applicable roles. In this development research, valid, practical, and effective e-learning products are produced. Expert validation shows an average assessment of 92%. The practicality of the application assessed by users in the aspects of appearance, material, discussion, and ease of access reached an average of 86.39%. The effectiveness of the application is also good when viewed from student learning outcomes, where it is known that 82% of students exceeded the target of lecture completeness.